2020
DOI: 10.1097/naq.0000000000000414
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Trust, Psychological Empowerment, and Organizational Commitment Among Licensed Practical Nurses

Abstract: In this study, we examine the influence of organizational trust on organizational commitment among licensed practical nurses (LPNs). Guided by prior research and theory, we also consider whether psychological empowerment mediates the influence of organizational trust on organizational commitment. To accomplish these tasks, we examine data from our survey of all registered LPNs in a Midwestern US state on their levels of organizational trust, psychological empowerment, and organizational commitment. Using path … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…The current results are in line with different studies that indicated on the importance of organizational trust in achieving better-engaged employees [18,104]. These results are consistent with different recent studies that tried to connect organizational trust with different work outcomes [105][106][107][108].…”
Section: Discussionsupporting
confidence: 93%
“…The current results are in line with different studies that indicated on the importance of organizational trust in achieving better-engaged employees [18,104]. These results are consistent with different recent studies that tried to connect organizational trust with different work outcomes [105][106][107][108].…”
Section: Discussionsupporting
confidence: 93%
“…However, despite the continuous call for an underlying process via which CER perceptions influence millennials' job-seeking intentions, little research has empirically examined the role of psychological factors in the above relationship [1,2]. Furthermore, while many researchers have focused on the effects of organizational trust on existing employees' performance and commitment (e.g., [3,4]), trust research on job-seeking literature for prospective employees is very limited. This suggests that the impacts of organizational trust are largely applicable to existing employees of an organization, leaving an important gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…In the discipline of nursing, trust is believed as one of nursing’s substantial assets and nurses have long been valued as someone who can be trusted; however, there are very limited scholarly works on the phenomenon of trust and living experience of feeling trusted in nursing. Many studies on trust in nursing are limitedly about either the specific trust of nurse-patient relationships, focusing on healthcare outcomes (Ozaras & Abaan, 2018; Polansky, 2019; Rutherford, 2014) or the influences of organizational trust on the level of nurses’ job performance, work satisfaction, job stress, or burnout (Loes & Tobin, 2020; Wei, Yaqing, & Lin, 2015; Williams, 2005). For example, Rutherford (2014) studied the value of trust to nursing and asserted that trust influences nurse-patient relationships and healthcare outcomes, indicating nursing’s attributes related to the nurse-patient trust such as “clinical competency, demonstrated compassion and goodwill, patient advocacy, patient vulnerability, and nurses’ moral duty” (p. 283).…”
Section: Unfolding the Conceptmentioning
confidence: 99%